Location of Retinal Nerve Fiber Layer Defects in Open-angle Glaucoma and Associated Factors - Kim, Han Ul (Korean journal of ophthalmology, 2019)
To investigate the location of retinal nerve fiber layer defects (RNFLDs) in open-angle glaucoma and the differences in systemic and ocular factors between superotemporal and inferotemporal RNFLDs. We performed a retrospective review of the 2008 to 2012 data from the Korea National Health and Nutrition Examination Survey. Subjects aged ≥19 years with an evaluable fundus photograph of at least one eye were enrolled, and open-angle glaucoma was diagnosed according to modified International Society of Geographical and Epidemiological Ophthalmology criteria. In subjects with open-angle glaucoma, locations of RNFLDs were evaluated, and systemic and ocular factors were compared between the bilateral superotemporal RNFLD group and bilateral inferotemporal RNFLD group. A total of 534 subjects had open-angle glaucoma with RNFLDs. The unilateral inferotemporal region (25.8%) was the most common location for RNFLDs, followed by the unilateral superotemporal region (24.4%). Multivariate analysis revealed that hypertension was more significantly associated ( = 0.048) with the bilateral superotemporal RNFLD group than with the bilateral inferotemporal RNFLD group. Superotemporal RNFLDs are more related to hypertension than are inferotemporal RNFLDs.